2004
DOI: 10.1159/000078778
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Phagocytosis and Metabolism Differ from Those of Macrophages

Abstract: The purpose of this study is to compare primary human retinal pigment epithelium (RPE) cells with respect to particle uptake and further processing steps with immunological phagocytes for a better understanding of the possible role of RPE cells in triggering autoimmune diseases in the eye. We investigated the similarities of human RPE and monocytes/macrophages studying the uptake of fluorescein- and europium-labeled synthetic microparticles and microbial pathogens by human and bovine RPE cultures and a permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…RPE are the most actively phagocytozing cells in the body. This process may lead to generation of ROS, although some work suggests that the process is different to that of macrophages (Irschick, et al, 2004). As the RPE ages, oxidation of lipids and other cellular components result in an accumulation of indigestible material lipofuscin in the lysosomes, leading to their enlargement and formation of lipofuscin granules.…”
Section: Mitochondrial Ros Systems and Maculopathymentioning
confidence: 99%
“…RPE are the most actively phagocytozing cells in the body. This process may lead to generation of ROS, although some work suggests that the process is different to that of macrophages (Irschick, et al, 2004). As the RPE ages, oxidation of lipids and other cellular components result in an accumulation of indigestible material lipofuscin in the lysosomes, leading to their enlargement and formation of lipofuscin granules.…”
Section: Mitochondrial Ros Systems and Maculopathymentioning
confidence: 99%
“…Wet AMD -the more advanced form of the disease -involves proliferation of blood vessels (neovascularization) through the blood-retina barrier and subretinal exudate formation (Green & Enger 1993). This stage is marked by professional phagocytes (macrophages and dendritic cells) involvement, the price of which is the accumulation of chemoattractant-rich drusen with the ability of initiating low-grade inflammation (Forrester 2003;Irschick et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We attribute this to the relatively small size of the used particles as compared to T lymphocytes and apoptotic cell material. In a previous study we found a size-dependent uptake in primary human RPE cultures as well as in ARPE-19 cells, showing a preferential uptake of smaller beads as compared to larger microbes [7] .…”
Section: Discussionmentioning
confidence: 71%
“…Additionally RPE cells were in contrast to macrophages not capable of inducing intracellular oxidative mechanisms upon ingestion of bacteria [7] although like in macrophages ␥ -interferon stimulation leads to induction of neopterin also in RPE cells [7] . The present study was undertaken to establish primarily whether a diurnal rhythm is involved in phagocytosis by human RPE cells.…”
Section: Introductionmentioning
confidence: 97%